2009
DOI: 10.1246/cl.2009.898
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectra of Isotope-substituted Mitochondria of Living Budding Yeast Cells: Possible Origin of the “Raman Spectroscopic Signature of Life”

Abstract: The 13 C and 2 H isotope substitution effects have been examined for the ''Raman spectroscopic signature of life,'' a mitochondrial Raman band at 1602 cm À1 that sharply reflects the metabolic activity of living yeast cells. The band shifts to 1542 cm À1 with 13 C substitution and to 1599 cm À1 with 2 H substitution. Normal mode analysis based on a DFT calculation suggests that it originates from a C=C double bond having no hydrogen atoms attached to the carbon atoms. The in-phase C=C stretch mode of ubisemiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
0
14
0
2
Order By: Relevance
“…In the past two decades, a number of publications have shown the successful application of Raman microspectroscopy to label-free molecular-level analysis of living cells and to discrimination of cell types. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Although Raman spectra contain rich information on molecular structure, detailed interpretation of measured spectra is often difficult because of their complexity. Each Raman spectrum obtained from space-resolved mapping measurements is usually interpreted as a superposition of several spectral components of biomolecules, as well as a background and fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, a number of publications have shown the successful application of Raman microspectroscopy to label-free molecular-level analysis of living cells and to discrimination of cell types. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Although Raman spectra contain rich information on molecular structure, detailed interpretation of measured spectra is often difficult because of their complexity. Each Raman spectrum obtained from space-resolved mapping measurements is usually interpreted as a superposition of several spectral components of biomolecules, as well as a background and fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of Raman spectroscopy for characterization the cell activity was demonstrated recently by series of studies [20][21][22][23]. Another outstanding application of the Raman spectroscopy for cells is the studies of the Raman spectra of cytochromes [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Isotope substitution experiments also showed that the signal originates from a C=C double bond structure [15]. The information above has helped us to finally propose sev- eral specific candidates of the "Raman spectroscopic signature of life" and we hope that the true origin of the signal will be elucidated soon.…”
Section: Resultsmentioning
confidence: 82%